1989
DOI: 10.1080/00913847.1989.11709707
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Responses to Treadmill and Water Running

Abstract: In brief: The physiologic responses to running on a treadmill and to running in water while wearing a buoyant vest were compared in seven uninjured runners. Ventilation, oxygen uptake, and respiratory quotient were significantly higher during treadmill running, whereas heart rate and perceived exertion were not significantly different for the two forms of exercise. Water running elicited a 36% lower metabolic cost than treadmill running despite the athletes' efforts to maintain a similar level of exertion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 5 publications
1
18
1
2
Order By: Relevance
“…Bishop et al, (1989) reported a higher O2 pulse during DWR compared with TMR. Similar results were found with the subjects in the present study in which O2 pulse during DWR was 4.34 and 3.81 during TMR (p<0.01).…”
Section: O2 Pulsementioning
confidence: 99%
“…Bishop et al, (1989) reported a higher O2 pulse during DWR compared with TMR. Similar results were found with the subjects in the present study in which O2 pulse during DWR was 4.34 and 3.81 during TMR (p<0.01).…”
Section: O2 Pulsementioning
confidence: 99%
“…An important factor in deep wawater running is the skill of the athlete. Studies have found the heart rate-V02 relationship and the rate of perceived exertion in deepwater running to be skill dependent (6,31). Those individuals who were less skilled used greater arm movement to maintain position in the water, thereby increasing their heart rate and rate of perceived exertion.…”
Section: Lmmersion and Exercise Responsementioning
confidence: 99%
“…For this reason, water walking and jogging are also effective exercises for individuals with body-weight problems and people of middle and advanced age. Many previous studies have reported metabolic and cardiorespiratory responses during walking and jogging in a pool (Evans et al, 1978;Whitley and Schoene, 1987;Bishop et al, 1989;Ritchie and Hopkins, 1991;Town and Bradley, 1991;Gehring et al, 1992), but it was difficult to fix the physical and physiological intensity for walking and jogging in a pool.…”
Section: Introductionmentioning
confidence: 99%